Hereditary neurocutaneous angioma: a new genetic entity?. Issue 6 (December 1979) - Zaremba, J; Stepień, M; Jelowicka, M; Ostrowska, D
Abstract : A family pedigree with a possible new genetic syndrome characterised by the presence of angiomas, systemic in nature, affecting particularly the skin and the central nervous system, is described. Angiomas of the CNS seem to have a marked tendency to bleed. The condition shows a clearly dominant mode of transmission, four subjects in three generations being affected. Differentiation from other conditions belonging to the vascular abnormalities subgroup of phakomatoses is presented.